MEANING EQUIVALENCE PROBLEMS IN TRANSLATING ENGLISH IDIOMS INTO UZBEK - Aytmuxamedova Durdona Jasur qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article investigates the challenges of achieving meaning equivalence in translating English idioms into Uzbek. Idioms represent deeply culture-bound linguistic expressions whose meanings cannot be understood from their individual components. The study analyzes the theoretical bases of equivalence in translation, identifies the major semantic and pragmatic problems that arise during idiom translation, and suggests appropriate strategies for ensuring communicative equivalence. The findings demonstrate that due to linguistic and cultural divergence between English and Uzbek, total equivalence is rarely possible. However, through cultural adaptation and functional substitution, translators can convey idiomatic meaning effectively to Uzbek audiences.